Promoting Islamic Education within Multicultural Brunei Society Following the Implementation of the Shariah Law in 2013 - Siti Nurzanah Haji Dullah; Shaikh Abdul Mabud (Dinamika Ilmu, 2024)
The Syariah Penal Code Order, 2013 (SPCO 2013) has formally become the law of Brunei Darussalam, with its first phase of implementation commencing on 1st May 2014. This paper aims to explore the impact of SPCO 2013 on Islamic Education in Brunei. Therefore, this study discusses the Brunei education system prior to and since the implementation of the SPCO 2013 and aims to provide a critical analysis of the action taken by the Brunei government to bring about changes in both its secular and religious schools. Mixed methods research is used to make more rigorous inferences about the research problems. Interviews have been conducted with the respective government officers for data collection. The data were collected and then analyzed using the thematic analysis technique, followed by descriptive quantitative analysis. The findings of this study indicate that the SPCO 2013 has had a significant impact on the Brunei Education Curriculum in both of its Public Schools and Religious Schools. Therefore, the findings conclude that curriculum revision was crucial to ensure that it was in line with Islamic teachings and did not contain any elements that contradicted Shariah law, and this also helps to promote awareness and avoid misconception of the SPCO 2013 among non-Muslim students who are an integral part of the Brunei society.